Characterizing MicroPure ultrasound detectability of mineralization-related echogenic foci in regenerate bone during tibial bone transport - Ze Zhang; Juan Li; Dong Wang; Hongjie Zhou; Yonghong Zhang (Frontiers in Medicine, 2026)
Background Early assessment of regenerate bone mineralization is essential for monitoring distraction osteogenesis and guiding clinical management during tibial bone transport. MicroPure ultrasound is an advanced imaging technique designed to enhance the visualization of microcalcifications in soft tissues; however, its detection characteristics and clinical value in regenerate bone remain unclear. This study aimed to explore the size and depth-related factors associated with MicroPure detectability and identify exploratory classification thresholds associated with MicroPure detectability of early mineralization-related echogenic foci in regenerate bone, and investigate their association with healing outcomes. Methods A retrospective study was conducted in 15 patients (16 tibiae) undergoing tibial bone transport for chronic osteomyelitis. Thirty-two ultrasound examinations were performed at 2 and 4 weeks after distraction initiation. A total of 1,976 mineralization-related echogenic foci identified on conventional B-mode ultrasound were analyzed, including 988 MicroPure-detectable and 988 MicroPure-undetectable echogenic foci. Maximum diameter and depth were compared between groups. Receiver operating characteristic (ROC) analysis was used to determine exploratory classification thresholds, and generalized estimating equations (GEE) were performed to evaluate factors independently associated with MicroPure detectability. Associations between early MicroPure-detectable MREF counts and healing index were evaluated using linear regression. Results MicroPure-detectable echogenic foci exhibited significantly smaller diameters and shallower depths than MicroPure-undetectable echogenic foci (both p < 0.001). ROC analysis identified exploratory classification thresholds of 1.25 mm for diameter (AUC = 0.886) and 0.925 cm for depth (AUC = 0.756). Both diameter (OR = 0.002, 95% CI 0.001–0.005) and depth (OR = 0.089, 95% CI 0.016–0.492) were independently associated with MicroPure detectability. At the tibia level, greater numbers of early MicroPure-detectable echogenic foci were significantly associated with lower healing indices in both transverse (R 2 = 0.511, p = 0.002) and longitudinal scans (R 2 = 0.380, p = 0.011). Conclusion MicroPure ultrasound showed greater detectability for smaller and more superficial mineralization-related echogenic foci in regenerate bone. In this cohort, exploratory classification thresholds of 1.25 mm for diameter and 0.925 cm for depth were identified, providing quantitative reference values for interpreting MicroPure findings during tibial bone transport. Furthermore, a greater burden of early MicroPure-detectable echogenic foci was associated with more favorable healing outcomes. These findings support the potential role of MicroPure ultrasound as a non-invasive tool for early mineralization assessment and monitoring during distraction osteogenesis.